EPIDEMIOLOGICAL PROFILE OF ACQUIRED SYPHILIS IN THE NORTHERN REGION OF BRAZIL FROM 2011 TO 2021 - Silva Serrão, Fernanda; Silva, Mariana Simão Costa da; Soares Leite, Daniela (Revista de Ciências da Saúde Nova Esperança, 2024)
Sexually transmitted infections are among society's most recurring public health dilemmas. Syphilis is aninfectious disease exclusive to humans, transmitted through unprepared sexual contact. It is estimated thatannually, 11 million new cases of syphilis occur in adults aged 15 to 49 years worldwide. The objective ofthe research was to identify the epidemiological profile of syphilis acquired in the states of the NorthernRegion of Brazil between the years 2011 and 2021. This is observational research with a quantitative andretrospective approach, with data collection from the SINAN available on DATASUS. Sociodemographicvariables were analyzed: sex, age, race, education level, and diagnostic criteria. It was found that between2011 and 2021, in the states of the Northern Region of Brazil, 50,810 cases of acquired syphilis werereported. The state of Amazonas had the highest notification rate with 18,709 (36.82%) cases, followed bythe state of Pará with 13,102 (25.79%) notifications and Tocantins with 6,728 (13.24%) reported cases. Theyear 2018 presented the highest incidence rate of the period, decreasing from 2019. Thus, the profile ofsyphilis acquired in the North Region was male individuals aged between 20 and 39 years, mixed race, withunknown education, and in relation to the diagnostic criteria, laboratory diagnosis presented the highest rateof notifications. In this way, the need to promote actions with the aim of clarifying sexual health and offeringeffective measures to combat syphilis in the most affected population is evident, as well as it is essential toreevaluate the mandatory fields for filling out the notification and investigation forms of the SINAN, as theyrepresent an essential source for determining health indicators.